Sustainability as a Collective Choice - Arias, Fabio; Quintero, Melissa (Sustainability in Debate, 2015)
This article argues that sustainability is a matter of collective choice. There is no definitive definition of what it means and standard procedure to achieve it. Sustainability is always ambiguous, and may be redefined in each context where it is applied. This feature of the sustainability becomes a matter of collective choice, where the results depend on the ability of society to solve common issues. Therefore, sustainability will be associated with deliberative spaces where interests and values are at stake, but success will be to the extent that such spaces address the causes of problems and not simply balance the competing interests.